2010
DOI: 10.1038/oby.2009.182
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Obesity and Breast‐feeding Practices Among White and Black Women

Abstract: Despite the increase in obesity among women of reproductive ages, few studies have considered maternal obesity as a risk factor for breast‐feeding success. We tested the hypothesis that women who are obese (BMI = 30–34.9) and very obese (BMI ≥35) before pregnancy are less likely to initiate and maintain breast‐feeding than are their normal‐weight counterparts (BMI = 18.5–24.9) among white and black women. Data from 2000 to 2005 South Carolina Pregnancy Risk Assessment Monitoring System (PRAMS) were used. The o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
72
7
6

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(97 citation statements)
references
References 48 publications
12
72
7
6
Order By: Relevance
“…11,15,16,[18][19][20][21][22][23] Of the 13 studies that evaluated BF duration, 10 found an association between maternal obesity or overweight and reduced duration of BF [17][18][19][20][21][23][24][25] (Table 1). For some of the studies, the results were heterogeneous (present for BF initiation but not duration, or vice versa), or the association was present only for specific population groups and not others.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…11,15,16,[18][19][20][21][22][23] Of the 13 studies that evaluated BF duration, 10 found an association between maternal obesity or overweight and reduced duration of BF [17][18][19][20][21][23][24][25] (Table 1). For some of the studies, the results were heterogeneous (present for BF initiation but not duration, or vice versa), or the association was present only for specific population groups and not others.…”
Section: Resultsmentioning
confidence: 99%
“…21 Similarly, 2 of the 10 studies that found an association between overweight=obesity and BF duration found these relationships significant only for Hispanics but not African Americans 19 and only white Americans but not African Americans. 21 Most of the studies in the review were conducted exclusively with white, European-origin women in spite of the diverse international locations (e.g., Canada, France, Russia), with the exception of the studies by Li et al 20 and by Kitsantas and Pawloski, 18 which had sizable Hispanic and African American groups. The Australian study by Oddy et al 24 had a small Asian and Aboriginal minority group.…”
Section: Ethnic and Racial Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Superiority of nutri onal status and BFD in Turkman children compare to other ethnic groups in north of Iran has been approved in previous studies 4,18 . Forste 19 and Liu 20 reported the low interest in BF in black women compared to non-black women and Jevi 21 was seen the BFD in black women less than in white women and Spanish women in USA. Several studies 22,23 approved the infl uence of immigra on on BFD.…”
Section: Discussionmentioning
confidence: 99%
“…Only 56% of mothers currently initiate breastfeeding in Ireland compared to 81% in the UK and over 91% in Scandinavian countries (2) . Higher maternal BMI has been negatively associated with breastfeeding duration (3,4) . Other significant risk factors for early termination of breastfeeding include young maternal age, smoking and family infant feeding practices (5,6) .…”
mentioning
confidence: 99%